2017
DOI: 10.15406/ijrrt.2017.03.00068
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Orbital Tumors in Children

Abstract: Orbital tumors in children are very rare and radiologic image, as magnetic resonance, is extremely important for correct diagnosis. We report six cases of different diagnosis of orbital tumors, comparing their images and clinical aspects. Radiologic images are essential for determine specific diagnosis in most cases of pediatric orbital pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…On the MRI scan of retinoblastoma, the mass was hyperintense in the vitreous at T1, hypointense at T2, with enhancement on T1 post-contrast. [1] In this case, MRI has confirmed that there was no intraocular mass; therefore, the diagnosis of retinoblastoma seems to be ruled out.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…On the MRI scan of retinoblastoma, the mass was hyperintense in the vitreous at T1, hypointense at T2, with enhancement on T1 post-contrast. [1] In this case, MRI has confirmed that there was no intraocular mass; therefore, the diagnosis of retinoblastoma seems to be ruled out.…”
Section: Discussionmentioning
confidence: 59%
“…In pediatrics, most of the type was embryonal type. [1], [9] Therapy given to the orbital tumors patients should be based on histopathological study and then treated according to the diagnostic protocol. Incisional biopsy was sufficient to be done because clear tumor margins are difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation